Type III hospital, as part of the Comprehensive Health System for the Coronel Gregorio Albarracín Lanchipa district - Tacna - Ponce Sagua, Marco Antonio (2014)
Objective: This is to develop the architectural design of the type III hospital in Colonel Gregorio Albarracin Lanchipa District, to overcome the shortage of health infrastructure, enabling better service, so a comprehensive health system and better quality of life for population. Method: For the study and development Descriptive research was used to obtain information on health issues in the field of study. Experimental design was also used, allow to propose an adequate hospital infrastructure for the city of Tacna. Finally interviews, l iterature exploration, photographic record and reliable cases projects were conducted. Results: The study site needs to improve care medical facilities and that has no infrastructure to specialized care, the same may have radii of service, catering to the population of districts closest to this, both in infrastructure and specialized equipment and other operations. The solution to this problem is to create a type III- notch health care , designed to provide comprehensive health care, their components Hospital: Promotion, prevention and recovery. Conclusions: In this respect the project proposes a change in terms of organizational  structure  of a hospital, which can achieve significant improvements in the health system. Interrelating health functions to the functions of prevention and health care, research and culture training thus reaching the expectations raised.